Towards a Safe Church: More Than a Lambeth Call - King, Fergus J. (Journal of Anglican studies, 2024)
This paper gives definitions of terms which have become critical in ensuring that Anglican churches minimize the risk of harm to all who are involved as practitioners or recipients of its ministries. This imperative is rooted in Scripture, not just the recent history or pronouncements of the Lambeth Conference 2022. The terms "Safeguarding", "Safe Ministry" and "Safe Church" (SC) are set out with reference to the "Lambeth Calls". This paper explores why such terms have come to the forefront of current theological praxis, notes historical iterations of such matters and asks why some Anglican churches or provinces may resist adopting this Lambeth Call. It offers both an apologetic for the universal adoption of SC practices and a scriptural and dominical mandate for them. The paper identifies theological and scriptural principles on which SC theory and practice might be grounded. Anglican churches and provinces are encouraged to develop a theory and practice of SC pertinent to their environment rather than adhere to abstract universal prescriptions which risk irrelevance amidst cultural and contextual particularity.